BODE Index and GOLD Staging as Predictors of 1-Year Exacerbation Risk in Chronic Obstructive Pulmonary Disease - Faganello, Marcia Maria; Tanni, Suzana Erico [UNESP]; Sanchez, Fernanda Figueiroa; Gelamo Pelegrino, Nilva Regina [UNESP]; Lucheta, Paulo Adolfo [UNESP]; Godoy, Irma de [UNESP] (Lippincott Williams & Wilkins, 2010)
Background: The body mass index/airflow obstruction/dyspnea/exercise capacity (BODE) index and global initiative for chronic obstructive]on, disease (GOLD) staging system are validated measures to define disease severity and to predict survival in chronic obstructive pulmonary disease (COPD). We aimed to investigate the influence of BODE classes (score: 0-2, 3-4, 5-7, and 7-10) and GOLD stages (I, II, III, and IV) oil the moderate/severe exacerbation occurrence risk in a cohort of 120 mild/very severe stable patients with COPD. Methods: Demographics, clinical evaluation, spirometry, peripheral oxygen saturation, body composition, 6-minute walking distance, dyspnea, and quality of life measurements were obtained at baseline. patients were followed Lip for I year or until death, and information on exacerbation was collected. Results: The median annual exacerbation rate was 0.8. Logistic regression showed that the relationship between the risk for moderate/severe exacerbations during a 1-year follow-Lip for the GOLD stage was odds ratio: 2.01; 95% confidence interval: 1.39-2.98 and for the BODE index was odds ratio: 2.08; 95% confidence interval: 1.27-3.61. The area under the receiver-operator curve to predict exacerbation during the 1-year follow-up was 0.69 for the GOLD stage and 0.62 for the BODE index. Adjusted multiple logistic regression selected only older age and lower peripheral oxygen saturation as risk factors for COPD exacerbation in the I-year follow-up, Conclusions: III summary, our study shows that unidimensional GOLD classification and Multidimensional BODE index staging systems seem to have similar clinical utility in predicting exacerbation ill ambulatory COPD patients with COPD. However, variables not included in both systems seem to be the main predictors of the exacerbation risk.
Keywords: BODE index; GOLD stage; Age; Hypoxemia; COPD exacerbation